Study on the moisture uniformity of paddy drying technology by employing air direction reversals - GAI Ling; WANG Jian-ping (浙江大学学报. 农业与生命科学版)
Effect of depth of grain bed, velocity of airflow, and cycle of airflow reversals on the moisture uniformity, drying rate and heat consumption of the paddy drying technology were studied. The results show that the moisture uniformity is mainly affected by airflow rate. An increase in airllow rate enhances moisture uniformity throughout the grain bed. The optimum drying parameters of the technology were obtained.